ChemInform Abstract: Palladium N‐Heterocyclic Carbene Catalysts for the Ultrasound‐Promoted Suzuki—Miyaura Reaction in Glycerol. Issue 37 (22nd August 2013) - Azua, Arturo; Mata, Jose A.; Heymes, Pauline; Peris, Eduardo; Lamaty, Frederic; Martinez, Jean; Colacino, Evelina
Abstract Novel palladium N‐heterocyclic carbene‐based complexes with 3, 4, 5‐trimethoxybenzyl, alkyl and sulfonate N‐substituents are synthesized and used as pre‐catalysts in the title reaction.